AKTIVITAS TEKTONIK RELATIF BERDASARKAN INDEKS GEOMORFIK DAERAH TANGKAPAN AIR CIHAUR KABUPATEN BANDUNG BARAT PROVINSI JAWA BARAT: RELATIVE TECTONIC ACTIVITY BASED ON GEOMORPHIC INDICES OF CIHAUR WATER CATCHMENT AREA WEST BANDUNG REGENCY WEST JAVA PROVINCE - Anggito Saputra; Murni Sulastri; Nana Sulaksana; P Paramarta Raditya Rendra (Universitas trisakti, 2022)
The Cihaur watershed is one of the interesting areas for study about morphotectonic. This area is an earthquake-prone caused by subduction zone and active fault. The methods used in this study are: lineament analysis, morphotectonic, and associate of lithology and tectonic activity. The lineament analysis show that the ridge lineament pattern of study area is dominantly oriented West-East, following to structural pattern of Java. The morphotectonic analysis used three geomorphic index: basin asymmetric factor (Af), valley width-to-high ratio (Vf), and mountain front sinuosity (Smf). Then all the geomorphic index calculated by average of five geomorphic indices became index of relative tectonic activity (IATR). The study area was divided into four parts: 1st Class (very high tectonic, 13.14% in area); 2nd Class (high, 8.88% in area); 3rd Class (moderate, 46.21% in area); and 4th Class (low, 15.62% in area). This IATR result show that Cihaur watershed was controlled by moderate tectonic activity. The lithology of the study area is divided into: volcanic rock, sedimentary rock, and lake sediment. Association with tectonic activity shows that sedimentary rocks were highly tectonic-very highly tectonic, the volcanic rocks were moderately tectonic-highly tectonic, and lake sediment was low tectonic.